(untitled) (Journal of the College of Basic Education, 2022)
Technical education plays an important role in the process of refining the behavior of learners through the practice of technical works and taste and identify through the workings of color through history and the extent of the impact of color and methods of operation began from the Stone Age to the art of post-modern taking a completely different way in dealing with color as well as in the way Treatment and use of color is no longer practiced according to the requirements of the pre-modern technical concepts before the Second World War and at the same time moved away from the traditional means associated with it, and the laws of authorship to take new ways in dealing with the material that allowed the field of nose S relative freedom from control restrictions and follow their own laws. This shift in the technical concept paved the way for the transformation of the material itself when the oil painting was introduced to materials that were not accepted or accepted in the artistic field. The nature of these materials and modern techniques necessitated the use of new color tools to control the color more freely and with multiple techniques. The methodological framework included: The importance of the research and the objective of the research Limits of research and definition of the most important terms. The theoretical framework was based on two topics: the first topic (Semiae) and the second topic (the postmodern intellectual postulates) and the most important indicators that resulted from the theoretical framework. The research procedures included the research methodology, the research community, the research sample, the research tool, To separate by analysis. The main findings and conclusions were: Samples (1, 2) showed fragmentation and centralization in the method of implementation of the work and this is related to the imaginary mental image of the student. The content of the expression forms concepts of advertising ideas in their contents and forms, and this is confirmed by postmodern arts Samples (1, 2) showed the freedom to use raw materials, colors and methods of implementation that removed the shape of the meanings of social and cultural reference. The concerns of color showed diversity and contrasted with the ideas of the art of postmodernism and one of the secretions and reflections of the postmodern society. Some of the works tried to carry out the idea of ​​skipping fashionable and ordinary by adopting architectural architectural form.